THE ETHICAL DEVELOPMENT OF AGRITOURISM IN PROTECTED TERRITORY PELAGA BADUNG BALI, INDONESIA - I Gusti Bagus Rai Utama; Christimulia Purnama Trimurti (Jurnal Manajemen dan Kewirausahaan, 2019)
This research is a basic research that confirms the ethics of sustainable tourism planning with the research objective of the establishment of ethics of developing agritourism in the boundaries of protected forest. The quantitative method is uses as primarily approach involving 230 respondents, and 32 informants as supplementary approach. The conclusions are the ethical development of agritourism in protected area in the case study of Pelaga Village ideally able to present open natural beauty, cultural-friendly, environmentally friendly, and conserve a unique tourist attraction, provide public facilities, telecommunication, restaurants, and market centers for agriproducts, the availability of transportation to the location, and provide public facilities